Metabolism and Disposition of Aditoprim in Swine, Broilers, Carp and Rats - Wang, Liye; Huang, Lingli; Pan, Yuanhu; Kuča, Kamil; Klímová, Blanka; Wu, Qinghua; Xie, Shuyu; Ahmad, Ijaz; Chen, Dongmei; Tao, Yanfei; Wan, Dan; Liu, Zhenli; et al. (Scientific reports, 2016)
Aditoprim (ADP) is a newly developed antibacterial agent in veterinary medicine. The metabolism and disposition of ADP in swine, broilers, carp and rats were investigated by using a radio tracer method combined with a radioactivity detector and a liquid chromatography/ion trap/time-of-flight mass spectrometry. After a single oral administration, more than 94% of the dose was recovered within 14 d in the four species. The urine excretion was dominant in swine and rats, making up 78% of the dose. N-monodesmethyl-ADP, N-didesmethyl-ADP, and 10 new metabolites were characterized. These metabolites were biotransformed from the process of demethylation, α-hydroxylation, N-oxidation, and NH2-glucuronidation. After an oral dose for 7 d, ADP-derived radioactivity was widely distributed in tissues, and high concentrations were especially observed in bile, liver, kidney, lung, and spleen. The radioactivity in the liver was eliminated much more slowly than in other tissues, with a half-life of 4.26, 3.38, 6.69, and 5.21 d in swine, broilers, carp, and rats, respectively. ADP, N-monodesmethyl-ADP, and N-didesmethyl-ADP were the major metabolites in edible tissues. Notably, ADP was detected with the highest concentration and the longest duration in these tissues. These findings indicated that ADP is the marker residue and the liver is the residue target tissue.
Keywords: Liver; Tissue Distribution; Rats; játra; Adenosine Diphosphate; trimethoprim; Trimethoprim; aplikace orální; kapři; Mass Spectrometry; kur domácí; adenosindifosfát; krysa rodu Rattus; Swine; Carps; Chickens; zvířata; tkáňová distribuce; chromatografie kapalinová; Administration, Oral; prasata; Chromatography, Liquid; hmotnostní spektrometrie; Animals